2007
DOI: 10.1111/j.1462-2920.2007.01351.x
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriophage influence Campylobacter jejuni types populating broiler chickens

Abstract: The characteristics that allow one Campylobacter jejuni genotype to succeed over another under the influence of bacteriophage predation have been examined in experimental broiler chickens following the observation that this succession appeared to occur in naturally colonized broiler chicken flocks. Examination of three C. jejuni strains from a single flock indicated that horizontal transfer of at least 112 kb of genomic DNA from strain F2C10 (bacteriophage sensitive) to strain F2E1 (bacteriophage insensitive) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
45
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(55 citation statements)
references
References 55 publications
(76 reference statements)
8
45
2
Order By: Relevance
“…A study carried out by Connerton et al (32) revealed that succession of Campylobacter during phage infection was due to new genotypes rather than development of resistance of the existing strains. Findings of other authors support these results (39,40). While susceptible strains might disappear after application of phages, nonsusceptible strains can easily grow and lead to a rise in Campylobacter counts subsequent to an initial reduction.…”
Section: Reduction Of Campylobactersupporting
confidence: 79%
“…A study carried out by Connerton et al (32) revealed that succession of Campylobacter during phage infection was due to new genotypes rather than development of resistance of the existing strains. Findings of other authors support these results (39,40). While susceptible strains might disappear after application of phages, nonsusceptible strains can easily grow and lead to a rise in Campylobacter counts subsequent to an initial reduction.…”
Section: Reduction Of Campylobactersupporting
confidence: 79%
“…Very little is known regarding the ecology of this pathogen in vivo, but it is evidently highly complex. It was demonstrated recently that bacteriophage populations alter the intestinal Campylobacter contingent (37). It is known that Campylobacter spp.…”
mentioning
confidence: 99%
“…The precise definition of the CI varies somewhat between studies, but the CI essentially measures the ratio of one strain to another in the model and compares it to that of the inoculum. This has been used to investigate succession of C. jejuni and Campylobacter coli (6), to examine the effect of bacteriophage on C. jejuni strains in chickens (32), and to compare the colonization ability of C. jejuni isolates (4,19,33), often with particular emphasis on the possibility of competitive exclusion as a control strategy. Comparisons of mutants versus wild type have also been used to demonstrate the importance of particular genes in colonization (25,34,38), to establish an advantage for fluoroquinoloneresistant bacteria in colonization even in the absence of antibiotic selection (22), and to validate an insertional gene expression system for C. jejuni (18).…”
mentioning
confidence: 99%